Experimental characterization and modelling of electromigration lifetime under unipolar pulsed current stress - Lim, Meng Keong (2013)
The electromigration behaviour of Cu/SiCOH interconnects carrying unipolar pulsed current with long periods (i.e. 2, 16, 32 and 48 h) is presented in this study. Experimental observations suggest that the electromigration behaviour during void growth can be described by the ON-time model and that the lifetime of the Cu/SiCOH interconnects is inversely related to the duty cycle. Numerical simulation is carried out to compute the time required to nucleate a void under unipolar pulsed current stress conditions. The time to void nucleation is found to vary proportionally to the inverse square of the duty cycle and is independent of frequency at 1 Hz and higher. By computing the stress evolution in interconnects with short length, it was shown that the product of the unipolar pulsed current’s duty cycle and current density, i.e. average current density, is equivalent to the current density of a constant current (D.C.) stress. The simulation results suggest (d · jL)crit as the equivalent critical current density-length product under unipolar pulsed current condition. Both the experimental and simulation results show that duty cycle has an effect on the electromigration lifetime of interconnects carrying unipolar pulsed current.